2008
DOI: 10.1074/jbc.m706009200
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Residues in the C-terminal Domain 2 Are Required for Nanog to Mediate LIF-independent Self-renewal of Mouse Embryonic Stem Cells

Abstract: Nanog was identified by its ability to sustain the LIF-independent self-renewal of mouse embryonic stem (ES) cells and has recently been shown to play a role in reprogramming adult fibroblasts into pluripotent stem cells. However, little is known about the structural basis of these remarkable activities of Nanog. We have previously identified an unusually strong transactivator named CD2 at its C terminus. Here we demonstrate that CD2 is required for Nanog to mediate ES cell self-renewal. Furthermore, deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Reporter assays demonstrated that deletion of WR had little effect on transcription activity of Nanog, whereas removal of CD2 reduced its activity severely, suggesting that WR is dispensable for Nanog function (15,16). Consistently, we demonstrated that CD2, apparently endowed by a few critical aromatic residues with its strong transactivation activity, is required for Nanog to mediate LIF-independent ES cell self-renewal (17). Unexpectedly, we recently proved that WR plays an important role in Nanogmediated LIF-independent ES cell self-renewal despite its apparent lack of contribution to Nanog transcription activity.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Reporter assays demonstrated that deletion of WR had little effect on transcription activity of Nanog, whereas removal of CD2 reduced its activity severely, suggesting that WR is dispensable for Nanog function (15,16). Consistently, we demonstrated that CD2, apparently endowed by a few critical aromatic residues with its strong transactivation activity, is required for Nanog to mediate LIF-independent ES cell self-renewal (17). Unexpectedly, we recently proved that WR plays an important role in Nanogmediated LIF-independent ES cell self-renewal despite its apparent lack of contribution to Nanog transcription activity.…”
supporting
confidence: 65%
“…Functionally, we were able to assign WR and CD2 as transactivators embedded in its C terminus (15,16). Our further analysis has demonstrated that CD2 is the dominant transactivator and that its activity is absolutely required for Nanog-mediated LIF-independent ES cell self-renewal (17). We report here that WNAAP from the WR domain appears to bind to Nac1 and impact the cell cycle machinery rather than the pluripotency maintenance or self-renewal function of ES cells.…”
Section: Discussionmentioning
confidence: 70%
“…The protein domain structure of Nanog has been studied extensively to elucidate its molecular mechanism of action. The C-terminal domain, including the tryptophan-rich (WR) domain, has been deemed essential for the function of Nanog (25)(26)(27)(28)(29); however, study of the N-terminal domain (NTD) has been largely overlooked to date.…”
Section: Embryonic Stem (Es)mentioning
confidence: 99%
“…2 g of total RNA was reverse transcribed in a final volume of 20 L as previously described [7] . Real-time reverse-transcriptase (RT)-PCR reactions were performed using the Real-time PCR Master Mix (SYBR GREEN) Reagent Kit (TOYOBO, QPK-201), according to the manufacturer's protocol.…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
“…Both the WR and CD2 are essential for the transcriptional activity and the maintenance of ES cell self-renewal in vivo [6][7][8] . However, the function of the ND has not been reported yet.…”
mentioning
confidence: 99%